Perceptions of Chinese Employees of Discriminative Ethnic Bias: a Study of British Born Chinese and Chinese Migrant Workers in British Organisations - CHENG, Biyun (2018)
This research aims to explore the ethnic equality and workplace diversity in the British organisations from the perceptions of British born Chinese and Chinese migrant workers. A qualitative method is employed to investigate this topic, interviews is the only data collection method to collect primary data, and then a thematic analysis is used to find the results. A total of eight individual interviews are conducted through face-to-face interviews, telephone interviews and online interviews. The participants are asked about their experiences of ethnic discrimination in workplaces and in daily life, their thoughts on the equality of promotion, bonus and so on. They are also invited to give suggestions to the institutions and their companies regarding ethnic equality. Then a comparison between the British born Chinese employees and Chinese migrant employees is made during the data analysis process. The results suggest that both two generations of Chinese employees are generally satisfied with the ethnic equality in the companies they work for, however, the subtle and implicit discriminations is not entirely eliminated. Meanwhile, work ability and professionalism are perceived as two important factors which help to reduce the ethnic inequality in workplaces. Furthermore, the findings also imply that British born Chinese and Chinese migrant workers have other concerns, which respectively are gender equality for ethnic minority female and the potential conflict and bias between Chinese migrant employees.